Recordkeeping Error or Strategic Seasonal Substitution?: The Seasonality of Occupational Injuries in SOII and MarketScan. Issue 3 (March 2022) - Raymond, Benjamin
Abstract : Objective: I compare the seasonal patterns observed in the Survey of Occupational Injuries and Illnesses (SOII) to claims data from the IBM ® MarketScan ® Research Databases. Methods: I construct monthly injury rates and claims rates by supplementing occupational injuries and other claims data with hours data from the Current Population Survey and estimate seasonal effects using an Unobservable Components Model. Results: While workers' compensation data and the SOII display similar seasonal patterns, the year-end decline in the MarketScan data is 1/3 to 1/2 the magnitude observed in the SOII. Short-term disability and private health insurance claims display seasonal patterns inversely related to occupational injuries. Conclusions: Part of the year-end decline in occupational injuries observed in the SOII is likely due to recordkeeping error. There is also some evidence of strategic seasonal substitution between various health-compensation alternatives. Abstract : This paper demonstrates workers' compensation claims and occupational injuries recorded in the SOII show a qualitatively similar seasonal trend. These seasonal patterns are inversely related to the seasonal fluctuations in short-term disability and private insurance claims. These findings have important implications for health care providers.